STRATEGI PENINGKATAN PENERIMAAN PAJAK KENDARAAN BERMOTOR (PKB) DALAM MENINGKATKAN PENDAPATAN KOTA MAKASSAR - Asriati, Asriati; Sasmito, Chanra (Perpustakaan dan Penerbitan Unismuh Makassar, 2014)
This study aims to determine the Strategy of Increasing Motor Vehicle Tax Acceptance (PKB) and its contribution to local tax revenue (PAD). The method used in this research is qualitative descriptive analysis method which describes the state of vehicle tax revenue and its contribution to local tax (PAD). Based on the results of the study, motor vehicle tax revenues in 2014, 2015 to 2016 continue to increase and in 2016 revenue Samsat region I Makassar increased very well until it passes the target set. The increase in vehicle tax revenues (PKB) contributes to local taxes (PAD) in 2014 of 311.83%, 2015 has a percentage of 372.87%, and in 2016 has a percentage of 400.45%.